Effectiveness of Group Psychotherapy in the Treatment of Obesity During Adolescence: A Prospective Controlled Study - Nurdan Tekgül (Galenos Publishing House, 2020)
INTRODUCTION: Group therapy as a different method in the treatment of obesity in adolescence; weight loss, eating habits, communication skills and emotional and behavioral problem levels in terms of evaluation. METHODS: The study is performed in University of Health Sciences, İzmir Tepecik Training and Research Hospital, Clinic of Family Medicine, Youth Counselling and Health Service Center. Two study groups were created from randomly selected 16 obes adolescents according to their BMI (Body Mass Index), between the ages of 13-18. Group I: eight adolescents who took sosyometric psikotravmatic group therapy for obesity treatment. Group II: eight adolescents who didn't take sosyometric psikotravmatic group therapy. A sosyometric psikotravmatic group therapy was applied that will take 8 weeks, 1 day per week in order to develop their communication skills. RESULTS: BMI (Body Mass Index) of those who continued therapy showed 100% reduction, while those who did not contribute had 25% in reduction. Especially their relations with their parents and relatingly their emotional distress was found to have a negative contribution to their eating habits. DISCUSSION AND CONCLUSION: Although the small sample suggests the reliability of our findings, this prospective study shows that; group therapies with young people are thought to increase the success in relation to the fact that they experience the power of group interaction independently of the subject. Studies on this subject can be repeated with a larger sample.